Developing Mission: Photography, Filmmaking, and American Missionaries in Modern China - Hong Guo; Xiaoyang Xiao (Journal of Dharma, 2025)
Joseph W. Ho’s Developing Mission makes a unique contribution to visual studies by taking a distinctive approach. The book examines how American missionaries in early to mid-twentieth-century China used photography and film to shape transnational ministry, construct cross-cultural identities, and capture the traumas of wartime. Ho’s in-depth critical analysis of these visual practices raises important questions about preservation and accessibility, while also charting a new course for future research. His work offers a fresh and compelling perspective, opening up intriguing avenues for further exploration in the field.